Effects of feeding different dietary net energy levels to growing-finishing pigs when dietary lysine is adequate - Sureemas Nitikanchana; Steven S Dritz; Michael D Tokach; Joel M DeRouchey; Robert D Goodband; Bradley J White (Kansas Agricultural Experiment Station Research Reports, 2014)
A total of 543 pigs (PIC 1050 × 327: PIC Hendersonville, TN) were used in 2 consecutive experiments with initial BW of 105 and 125 lb in Experiments 1 and 2, respectively. The objective was to validate the regression equations predicting growth rate and feed efficiency of growing-finishing pigs based on dietary NE content by comparing actual and predicted performance. Thus, the 5 treatments included diets with: (1) 30% dried distillers grains with solubles (DDGS), 20% wheat middlings, and 4 to 5% soybean hulls (low-energy); (2) 20% wheat middlings and 4 to 5% soybean hulls (low-energy); (3) a corn-soybean meal diet (medium-energy); (4) diet 2 supplemented with 3.7% choice white grease (CWG) to equalize NE level to diet 3 (medium-energy); and (5) a corn-soybean meal diet with 3.7% CWG (high-energy). In Experiments 1 and 2, increasing dietary NE increased (linear, P<0.01) final weight, ADG, and improved feed efficiency but decreased (P<0.11) ADFI. Only small differences were observed between the predicted and observed values of ADG and feed efficiency, except for the low-energy diet containing the highest fiber content (30% DDGS, wheat middlings and soy hulls; diet 1). Carcass weight and carcass yield increased (linear, P = 0.01) with increasing dietary NE. Also, backfat depth increased (linear, P = 0.01), loin depth decreased (quadratic, P = 0.05), and lean percentage decreased (linear, P = 0.01) with increasing dietary NE (linear, P = 0.01). Jowl iodine value (IV) also decreased with increasing dietary NE. No differences (P>0.26) in net energy caloric efficiency (NEE) on a live weight basis were observed with increasing dietary NE. Nevertheless, feeding 30% DDGS (diet 1) resulted in a poorer (P = 0.05) NEE on a carcass basis compared with feeding the other diets. In conclusion, the prediction equations provided a good estimate of growth rate and feed efficiency of growing-finishing pigs fed different levels of dietary NE except for the pigs fed low-energy diet containing highest fiber content (diet 1). These predictions of growth performance can be used to model the economic value of different dietary energy strategies.; Swine Day, Manhattan, KS, November 20, 2014
Keywords: Swine Day; 2014; Kansas Agricultural Experiment Station contribution; no. 15-155-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1110; Growth; Growing-finishing pig; Net energy; Regression